Coordinated induction of cell survival signaling in the inflamed microenvironment of the prostate. Issue 8 (24th February 2016) - McIlwain, David W.; Zoetemelk, Marloes; Myers, Jason D.; Edwards, Marshé T.; Snider, Brandy M.; Jerde, Travis J.
Abstract : PURPOSE: Both prostate cancer and benign prostatic hyperplasia are associated with inflammatory microenvironments. Inflammation is damaging to tissues, but it is unclear how the inflammatory microenvironment protects specialized epithelial cells that function to proliferate and repair the tissue. The objective of this study is to characterize the cell death and cell survival response of the prostatic epithelium in response to inflammation. METHODS: We assessed induction of cell death (TNF, TRAIL, TWEAK, FasL) and cell survival factors (IGFs, hedgehogs, IL−6, FGFs, and TGFs) in inflamed and control mouse prostates by ELISA. Cell death mechanisms were determined by immunoblotting and immunofluorescence for cleavage of caspases and TUNEL. Survival pathway activation was assessed by immunoblotting and immunofluorescence for Mcl−1, Bcl−2, Bcl−XL, and survivin. Autophagy was determined by immunoblotting and immunofluorescence for free and membrane associated light chain 3 (LC−3). RESULTS: Cleavage of all four caspases was significantly increased during the first 2 days of inflammation, and survival protein expression was substantially increased subsequently, maximizing at 3 days. By 5 days of inflammation, 50% of prostatic epithelial cells expressed survivin. Autophagy was also evident during the recovery phase (3 days). Finally, immunofluorescent staining of human specimens indicates strong activation of survival proteins juxtaposed to inflammation in inflamed prostate specimens. CONCLUSIONS: The prostate responds to deleterious inflammation with induction of cell survival mechanisms, most notably survivin and autophagy, demonstrating a coordinated induction of survival factors that protects and expands a specialized set of prostatic epithelial cells as part of the repair and recovery process during inflammation. Prostate 76:722–734, 2016 . © 2016 Wiley Periodicals, Inc.